2006
DOI: 10.1161/circulationaha.106.621854
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products

Abstract: Abstract-Advanced glycation end products (AGEs) are proteins or lipids that become glycated after exposure to sugars.AGEs are prevalent in the diabetic vasculature and contribute to the development of atherosclerosis. The presence and accumulation of AGEs in many different cell types affect extracellular and intracellular structure and function. AGEs contribute to a variety of microvascular and macrovascular complications through the formation of cross-links between molecules in the basement membrane of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
864
2
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,915 publications
(906 citation statements)
references
References 142 publications
17
864
2
23
Order By: Relevance
“…Our data suggest an additive increase in the expression of ICAM‐1 after exposure to irreversibly glycated albumin and pathological shear stress, which is in agreement with our previous findings14. Previously, it has been reported that AGEs can mediate an enhancement of ICAM‐1 expression both in vivo and in vitro 4. Furthermore, ICAM‐1 expression has been shown to be sensitive to shear stress in vitro 9, and in vivo ICAM‐1 expression is most pronounced at locations of disturbed wall shear stress20.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data suggest an additive increase in the expression of ICAM‐1 after exposure to irreversibly glycated albumin and pathological shear stress, which is in agreement with our previous findings14. Previously, it has been reported that AGEs can mediate an enhancement of ICAM‐1 expression both in vivo and in vitro 4. Furthermore, ICAM‐1 expression has been shown to be sensitive to shear stress in vitro 9, and in vivo ICAM‐1 expression is most pronounced at locations of disturbed wall shear stress20.…”
Section: Discussionsupporting
confidence: 93%
“…AGEs are heterogeneous compounds that alter cellular effects through the receptor for advanced glycation end‐products (RAGE). AGE–RAGE interactions induce the generation of reactive oxygen species and the activation of nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB)4. This leads to the enhanced expression of adhesion molecules (inter‐cellular adhesion molecule [ICAM‐1], vascular cell adhesion molecule [VCAM‐1]) and pro‐inflammatory cytokines (interleukin‐1, interleukin‐6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, hyperglycemia is linked to subsequent formation of non‐enzymatic glycosylation products, and further gives rise to advanced glycosylation end‐products (AGEs). These AGEs increase cross‐linking in collagen, tendons and ligaments, making these structures stiffer and weaker4. In addition, AGEs interact with their receptors on the surface of tenocytes and fibroblasts, thereby inducing inflammatory changes4.…”
mentioning
confidence: 99%
“…These receptors initiate maladaptive changes by initiating certain intracellular pathways, which disrupt cellular function. Advanced glycation end products-receptors for advanced glycation end products (AGE-RAGE) axis is now recognized to be an important pathway through which diabetes contributes to vascular damage [58]. …”
Section: Therapiesmentioning
confidence: 99%